Oedipus king: preparing man for the polis - José Joaquim Pereira Melo; Renan Willian Fernandes Gomes (Universidade Federal de Santa Maria, 2013)
Having Sophoclean play Oedipus King as a frame of reference, the purpose of this paper is to discuss the educative proposal conceived to the Greek Man as preparation for life in the polis. Although not intentionally, Sophocles pointed out an ideal of Man which, in his perspective, would fulfill Greek societal demands of that time. Such society was divided between myth and rationality and, as a result, Man found Himself in conflict and lacking direction for His life. Given that, Oedipus' character represented the ideal behavior of that society, and it also made it possible for citizens to reflect and to discuss social, economic and political transformations taking place at that period. Thus Sophocles came up with a hero who was an educational model and a citizen's as well. Furthermore, such hero differed from that one of the archaic Greek thought.